Perioperative registries in resource-limited settings: The way forward for Pakistan - Waqar, Usama; Shaheer Ahmed; Ayesha Nasir Hameed; Namrah Aziz; Hina Inam (Journal of the Pakistan Medical Association, 2022)
Capable of improving surgical quality, perioperative registries can allow performance benchmarking, reliable reporting and the development of risk-prediction models. Well established in high-income countries, perioperative registries remain limited in lower- and middle-income countries due to several challenges. First, ensuring comprehensive data entry forums to power the registries is difficult because of limited electronic medical records requiring sustained efforts to develop and integrate these into practice. Second, lack of adequate expertise and resources to develop and maintain registry software necessitates the involvement of software developers and information technology personnel. Third, case ascertainment and item completion are challenging secondary to poor-quality medical records and high lossto- follow-up rates, requiring telemedicine initiatives as an adjunct to existing care for the assessment of postdischarge outcomes. Continuous...